MELLEM CHIC AGO OG OUJDA: To perspektiver på marokkansk social struktur - Schade-Poulsen, Marc (Tidsskriftet Antropologi, 2019)
Marc Schade-Poulsen: Between Chicago and Oujda. Two Perspectives on Moroccan Social Structure This article deals with American anthropologists’ descriptions of Moroccan social structure in the 1960s and 1970s: Eickelman, Geertz, Rabinow, Rosen, and Crapanzano. Thirty years later during a field trip to Oujda, North Eastem Morocco, the author found similar descriptions of Moroccan social structure as expressed by young, male candidates for migration to Europe. The article describes the changes that have occurred in Morocco during the last thirty years. It compares the early American anthropological point of view with the more recent Moroccan one. It concludes that if the early American “school” had been less inclined to interpretive, symbolic approaches to Moroccan society, and more eager to listen to individual Morrocans’ hopes for their future, it would not have been so easy to describe Morocco as a "bargaining society”. Rather, it would have included an analysis of Moroccan power relations that are being challenged by today’s globalisation.